Pengembangan Media Pembelajaran Interaktif Berbasis Microsoft Power Point Kelas V Sekolah Dasar - Sofiyan Sofiyan (Program Studi PGSD Kampus UPI di Serang, 2021)
This study aims to produce interactive learning media products based on Microsoft Power Point to improve student learning outcomes in the Thematic learning with the theme Healthy Is Important, the sub-theme My blood circulation is healthy in fifth grade elementary school. The research method used is the research of Borg and Gall which includes: preliminary studies, model development and model testing. The results showed that the developed interactive learning media was declared feasible. Media validation and material validation showed an average score of 82.50% and 79.16%, respectively. Student responses to interactive teaching materials scored 81.75% in the small-scale trial while the large-scale trial obtained a score of 85%. Teacher responses scored 71.7% and 89.13%. Based on the value obtained, the interactive learning media based on Microsoft Power Point is feasible to be applied to fifth grade elementary school students.